Special International Tribunal on the investigation of the russian aggression against Ukraine: legal analysis, international jurisdiction and challenges - A. V. Voitsikhovskyi; O. S. Bakumov (Bulletin of Kharkiv National University of Internal Affairs)
The article is one of the first attempts to provide a comprehensive study of the theoretical and practical foundations for the scientific idea of establishing a Special International Tribunal on investigation of the russian aggression against Ukraine and determining its place in the system of international criminal justice.